Load Shedding Analysis using Under Frequency Relay (UFR) at Bolangi Substation using ETAP Software - Rezky Ramadhani; Yunus Tjandi; Zulhajji; Muh. Iswal Burhan (PT. Global Research Collaboration, 2025)
This study aims to analyze the performance of the load shedding system using Under Frequency Relay (UFR) at the Bolangi Substation as an effort to maintain the stability of the power system frequency. A supply disruption from Bayline Daya Baru (#2) occurred, namely a disturbance due to a lightning strike, which is an important background in this study. A decrease in frequency due to power imbalance can cause a total power outage (blackout), so a responsive UFR protection system is needed. Simulations were carried out using ETAP 19.0 software with a bayline release scenario to analyze the frequency response and effectiveness of automatic load shedding. The simulation results show that a frequency decrease of up to 48.60 Hz can be restored to 50 Hz in 2.47 seconds through gradual load shedding of 13.34 MW by UFR stages 2 and 4. This study provides an overview of the load shedding stages based on the frequency setting values ​​and periodic UFR working times as well as the use of ETAP for continuous evaluation of the protection system at the substation.